Repositioning the Authority of the Hajj Financial Management Agency (BPKH) Following the Establishment of the Ministry of Hajj: An Analysis of Independence and Accountability in Hajj Fund Management - Zakiruddin, Muhammad Aziz; Cecep Soleh Kurniawan (ASAS, 2026)
Previous studies on the Indonesian Hajj Financial Management Agency (BPKH) have largely focused on governance, accountability, and investment management under the regulatory framework preceding the establishment of the Ministry of Hajj. Limited attention has been paid to the repositioning of BPKH following the enactment of Law Number 14 of 2025 concerning the Organization of Hajj and Umrah. This study aims to analyze the functions and authority of BPKH in managing Hajj finances after the establishment of the Ministry of Hajj. This research employs a normative legal method using statutory, conceptual, and analytical approaches. The findings indicate that Law Number 14 of 2025 maintains BPKH’s role as the manager of Hajj finances and expands its involvement in determining the Hajj Operational Cost (BPIH). However, such reinforcement is mainly functional, while strategic authority is increasingly centralized under the Minister of Hajj. As a result, BPKH’s position has shifted from a relatively independent institution to a supporting institution within the Hajj governance system. The study also identifies potential issues of split authority, overlapping responsibility, and ambiguity of accountability between BPKH and the Ministry of Hajj. This study contributes to the discourse on Hajj governance by highlighting the institutional implications of the new regulatory framework and emphasizing the need for clearer authority arrangements and regulatory harmonization